2001
DOI: 10.3201/eid0703.017325
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Phage Associated with Recent Pandemic Strains ofVibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus, a halophilic gram-negative rod, causes seafood-borne gastroenteritis in humans. Infections caused by this organism have been associated with diverse serovars: 13 O serotypes and 75 K serotypes have been identified. Recent studies, however, have revealed the emergence and pandemic spread of a single serovar, O3:K6 (1-6). Strains belonging to the O3:K6 serovar abruptly appeared in India in 1996 and have since been isolated in Southeast Asian countries, from travelers at quarantine statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Previous studies demonstrated a strong association of filamentous phages, f237, with recent pandemic strains of V. parahaemolyticus. This phage possesses a unique ORF8 open reading frame that is found only in recent pandemic isolates, and the Zot (Zonula occludens toxin)-like toxin previously described in the V. cholerae is reported to be encoded in the ORF7 [51,52]. A match was found between the CRISPR spacer region of V. anguillarum PF7 with a zot-encoding prophage in V. anguillarum PF4, indicating the contribution of CRISPR to the phage resistance of this bacterium [53].…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies demonstrated a strong association of filamentous phages, f237, with recent pandemic strains of V. parahaemolyticus. This phage possesses a unique ORF8 open reading frame that is found only in recent pandemic isolates, and the Zot (Zonula occludens toxin)-like toxin previously described in the V. cholerae is reported to be encoded in the ORF7 [51,52]. A match was found between the CRISPR spacer region of V. anguillarum PF7 with a zot-encoding prophage in V. anguillarum PF4, indicating the contribution of CRISPR to the phage resistance of this bacterium [53].…”
Section: Discussionmentioning
confidence: 78%
“…Only three temperate phages have been associated with the pandemic strain. The temperate Inoviridae phage f237 is found integrated in most bacterial pandemic isolates providing its characteristic orf8, an open reading frame (ORF) used as a marker of pandemic strains (Nasu et al, 2000;Iida et al, 2001). Two other temperate myovirus phages were recently reported (Lan et al, 2009;Zabala et al, 2009); both belong to a fairly new group of telomeric phages.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the sequence of this region, PCR primers were designed that specifically amplify a fragment in the pandemic strain. Further, a filamentous phage (f237) has been reported to be associated with pandemic strains of V. parahaemolyticus (Nasu et al ., 2000;Iida et al ., 2001). Genetic analysis of this phage has revealed that the sequence of eighth open reading frame (ORF8) of f237 is found only in O3:K6 pandemic strains of V. parahaemolyticus isolated after 1996 outbreak.…”
Section: Introductionmentioning
confidence: 99%